Georgia Architectural and Historic Properties Survey of Rural [247] Midwestern section of the county , Valdosta, Ga. December 1980. - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Rural [247] Midwestern section of the county , Valdosta, Ga. December 1980. A one story saddlebag, rectangular plan with gabled tin roof and clapboard siding. Shed porch with turned spindle posts and gingerbread trim. Sash windows with 2/2 lights. Interior chimney, brick piers. Fair condition. Date of Construction: 1900. A typical saddlebag common to this area.
Georgia Architectural and Historic Properties Survey of Rural [247] Midwestern section of the county , Valdosta, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 1.27 MB (1,334,087 bytes).
Keywords: Historic buildings; Real property surveys; Brooks County (Ga.); Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)